E-Postpartum mobile application to increase postnatal knowledge care - Khairunnisa, Refa'; Sumarni, Sri; Supriyana, Supriyana (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Background: During this pandemic, maternal health services must still be considered because it is feared that there will be an increase in postpartum maternal morbidity and mortality. Postpartum care knowledge is vital for postpartum mothers to maintain their condition, so it is necessary to make an application that helps mothers through the E-Postpartum application. Objective: The study aims to develop and test the E-Postpartum mobile application to increase knowledge of postnatal care. Method: This study employed Research & Development consisting of 4 stages, namely Literature Study, Development Stage, Validity Expert, and Trial. Results: The E-Postpartum mobile application has six features, starting from education about postpartum care to consultation. The trial results showed that the application effectively increased the knowledge and action of postpartum mothers (p <0.001). Conclusion: The E-Postpartum application is beneficial for health workers in providing education, especially for postpartum mothers in carrying out care during the postpartum period. This postpartum application will make it easier for mothers to check their condition and make it easier for midwives to detect early and control the mother's condition even remotely.